Life Cycle Assessment of Sugar Industry Supply Chain: A Comprehensive Analysis of Environmental Impacts: Penilaian Siklus Hidup Rantai Pasokan Industri Gula: Analisis Komprehensif Dampak Lingkungan - Atikha Sidhi Cahyana; Iis Sugiarti; Inggit Marodiah; Intan Rohma Nurmalasari (Universitas Muhammadiyah Sidoarjo, 2023)
This scientific article aims to address the pressing issue of food wastage, known as